1980
DOI: 10.1002/app.1980.070251102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight distribution of poly(oxytetramethylene)glycol on cut growth resistance of polyurethane

Abstract: SynopsisA new method is proposed to improve the cut growth resistance of polyether-based polyurethane elastomers, i.e., polyethers used in this method are characterized by a double-humped distribution of molecular weight (DHDM), prepared by blending low-molecular-weight components and highmolecular-weight ones. The measurements of stress-strain curves, viscoelastic properties, and DSC thermograms of polyurethane elastomers before and after fatigue tests indicate that the destruction of the super molecular stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This is consistent in a general way with some early results for polyurethane elastomers. 101 Specifically, cyclic elongation measurements on unimodal and bimodal networks indicated that the bimodal ones survived many more cycles before the occurrence of fatigue failure. A schematic representation of this is shown in Figure 12.…”
Section: Characterization Of Upturns In the Modulus -mentioning
confidence: 99%
“…This is consistent in a general way with some early results for polyurethane elastomers. 101 Specifically, cyclic elongation measurements on unimodal and bimodal networks indicated that the bimodal ones survived many more cycles before the occurrence of fatigue failure. A schematic representation of this is shown in Figure 12.…”
Section: Characterization Of Upturns In the Modulus -mentioning
confidence: 99%
“…Further work is required to detail these predictions for TPUs. 6. Fracture surface morphology of the failed samples showed two distinct regions : a flat featureless region with an apparent fast cut growth and a rough undulate region with an apparent slow cut growth.…”
Section: Resultsmentioning
confidence: 98%
“…From Equation (2): then, or for an initial crack of c. length growing to a c length in a N number of cycles. Equation [6] predicts that the number of cycles to failure decreases as a function of the strain energy density W. Materials with high energy density values should show higher cut growth rates and lower cycles to failure. These predictions work for elastomers as has been shown by different authors [11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation